Geochronology and petrogenesis of granitoids and associated mafic enclaves from Xiate in Chinese Southwest Tianshan: Implications for early Paleozoic tectonic evolution - Gou, Long-Long; Zhang, L. (2016)
© 2015 Elsevier Ltd. Mineral compositions, in-situ zircon U-Pb and Hf isotopes, and whole-rock major-trace elements and Sr-Nd isotopes are reported for the host granitoids and associated mafic microgranular enclaves (MMEs) in Dongdeguli valley, and the Changawuzi mylonitic pluton, in the Southwest Tianshan, NW China. The Dongdeguli host granitoids have LA-ICP-MS zircon U-Pb ages of 446±2Ma and 443±3Ma, which are comparable with those (436±6Ma and 446±23Ma) of their enclaves. Both the host granitoids and MMEs have relatively high initial 87Sr/86Sr ratios and negative eopenNd(t) values. The MMEs are enriched in large ion lithophile and light rare earth elements but depleted in high field strength elements, and they are interpreted as melts derived from the fluids/melts metasomatized mantle wedge. The emplacement of mafic arc magma is inferred to cause the partial melting of ancient crust of Yili-Central Tianshan Block, which formed the granitic magma. Magma mixing model is proposed for the origin of the host granitoids and their mafic enclaves in the Dongdeguli valley. The Changawuzi mylonitic pluton has a SHRIMP zircon U-Pb age of 453±4Ma. It has relatively low SiO2 content, high MgO content, and negative whole-rock eNd(t) values and zircon eopenHf(t) values, with two-stage Nd model ages of 1.67-1.7Ga and two-stage Hf model ages of 1635-1760Ma, respectively. These results indicate that the Changawuzi mylonitic pluton was derived from partial melting of Paleoproterozoic crustal rocks, with involvement of some mantle-derived magma. The Dongdeguli granitoids and associated MMEs, and the Changawuzi mylonitic pluton, were formed by the northward subduction of paleo-South Tianshan oceanic crust in the Late Ordovician-Early Silurian period.